2000
DOI: 10.1002/tt.3020060305
|View full text |Cite
|
Sign up to set email alerts
|

A review of condition monitoring and fault diagnosis for diesel engines

Abstract: Technical advances and environmental legislation in recent years have stimulated the development of a number of techniques for condition monitoring and fault diagnosis (CMFD) in diesel engines. This paper firstly summarises common faults, fault mechanisms and their effect on diesel engine performance. Corresponding measurands are presented. Standard CMFD methods for parameters and CMFD systems for diesel engines are reviewed. Finally, some advanced CMFD techniques, including neural networks and fuzzy logic, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 57 publications
0
35
0
1
Order By: Relevance
“…There are many approaches used for internal combustion condition monitoring and fault diagnostic systems, such as Ferrographic Oil Analysis, Rotary Particle Depositor (RPD), Particle Quantifier (PQ), Spectrometric Oil Analysis, Image Analyser Systems, Contamination, Diesel Engine Fault Diagnosis (DEFD) system of Lloyd's Register, Knowledge-Based system for Marine Engine Diagnosis (KBMED), and Condition/Performance Monitoring and Predictive System for Diesel Engines (CPMPS) [2]. CPMPS is the current most powerful performance analysis based engine diagnostic method.…”
Section: Basic and Accumulated Performance Deviationmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many approaches used for internal combustion condition monitoring and fault diagnostic systems, such as Ferrographic Oil Analysis, Rotary Particle Depositor (RPD), Particle Quantifier (PQ), Spectrometric Oil Analysis, Image Analyser Systems, Contamination, Diesel Engine Fault Diagnosis (DEFD) system of Lloyd's Register, Knowledge-Based system for Marine Engine Diagnosis (KBMED), and Condition/Performance Monitoring and Predictive System for Diesel Engines (CPMPS) [2]. CPMPS is the current most powerful performance analysis based engine diagnostic method.…”
Section: Basic and Accumulated Performance Deviationmentioning
confidence: 99%
“…Traditionally engine maintenance is carried out as per the plan developed by the manufacturer and since this method can turn out to be post-failure maintenance in several cases, the condition monitoring maintenance has become more popular [1]. Jones and Li [2] have summarized that the main consequence of faults in diesel engines as the power loss, emission quality deterioration, noise and vibration, and thermal overload in cylinder. Generally, the causes of fault, the fault consequence and performance parameters measured for typical condition monitoring operations for a diesel engine are shown in figure 1.…”
Section: Iintroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Condition monitoring and fault diagnosis represent a valuable set of methods designed to ensure that the engine stays in good condition during its lifecycle, [7] and [13]. Diagnosis in the context of diesel engines is not new and various approaches have been proposed in the past years, however, recent technical and computational advances and environmental legislation have stimulated the development of more efficient and robust techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A topical review on different fault diagnosis methods for condition monitoring can be found in [7]. Both standard methods (Fourier analysis of pressure, torque, power, crankshaft speed and vibration signals) and advanced methods (neural networks, fuzzy techniques) are encountered and briefly described.…”
Section: Introductionmentioning
confidence: 99%